Property Of A Noblewoman - Steel, Danielle (Grand Haven, MIC Brilliance Audio, 2016)
"Property of a Noblewoman is the fascinating, moving new novel from Danielle Steel, whose many #1 New York Times bestselling tales have made her one of America's most beloved writers"--
Adult.
Adult.
Keywords: Young women -- Fiction